Knowledge and practice of nursing students on health care ethics - Wan Mohd Annuar, W Solihatul Hafidzah; Saat, Nur Hikmah; Razali, Muhammad Taufiq Atsifa; Aung, Khin Thandar (Scholars Academic and Scientific Publisher, 2017)
The nursing students are responsible for gaining knowledge about health care ethics and all nursing institutions or colleges either in worldwide or in Malaysia made ethics, moral and laws are included in their education system. The aim of the study is to assess the knowledge and practices of nursing students in health care ethics at International Islamic University Malaysia (IIUM) Kuantan. A cross-sectional study was conducted using a self-administered structured questionnaire to assess the nursing students’ knowledge in basic health ethics concepts with 15 multiple choice questions. Good knowledge was measured by a score ≥50% in the knowledge assessment test. Regarding on the practice of nursing students in health care ethics was assessed with 8 questions and scored using a Lkert scale. The findings of this study revealed that out of 128 nursing students, overall, 91 (71.1%) scored ≥50% in the healthcare ethics knowledge test and 116 (90.6%) nursing students are exhibited in a good level of practice in health care ethics. There was an association between gender and level of knowledge (p=0.005) and between their CGPA and level of knowledge (p= 0.001) while there was no association between all demographic characteristics and level of practice and there was no association between level of knowledge and level of practice (p>0.005). Mostly, the nursing students at Faculty of nursing, IIUM are exhibited good knowledge and practice in health care ethics. Therefore, it is recommended that it is needed to maintain and improve the structured teaching learning methods for nursing students regarding health care ethics to address basic concepts in nursing ethics and its application in clinical practice.